G446 Highly elevated ferritin levels are associated with haemophagocytic lymphohistiocytosis – are we missing treatable diagnoses? a retrospective service evaluation of diagnosis in patients with ferritin >10, 000 μg/l. (12th March 2018) - Sen, E; Moran, L; Almeida, B; Close, R; Bennett, J; Anderson, C; Deepak, S; Tattersall, R
Abstract : Background: Haemophagocytic lymphohistiocytosis (HLH) is a hyperinflammatory syndrome which can complicate sepsis, malignancy or autoimmune disease and may lead rapidly to critical illness and death. Early treatment reduces mortality but diagnosis requires a high index of suspicion and correct interpretation of laboratory results. Highly elevated ferritin levels (HEF) >10, 000 µg/L are highly specific for HLH and should prompt consideration/exclusion of hyperinflammation. Diagnostic guidelines for HLH were published in 2004 requiring the presence of ≥5/8 criteria. Aim: To assess recognition of HLH in a paediatric population with HEF. Methods: This retrospective study was conducted at 8 UK centres. Biochemistry databases identified patients≤16 years with serum ferritin >10, 000 µg/L between 01.04.2014 and 31.03.2017. A standardised proforma was used to collect data. Cases were assessed against the 2004 HLH criteria. Due to limited access to some laboratory tests, modified criteria using a threshold of ≥4/5 (excluding tissue haemophagocytosis, decreased natural killer cell function, increased soluble interleukin-2 receptor) were also applied. Results: Ninety-four patients (60.6% male) were identified. 36% were aged <1 year, 16% 1–5 years, 34% 6–12 years and 14% 13–16 years. Management was in neonatal/paediatric intensive care in 49.4%. Diagnoses included: infections (29.8%), malignancies (21.3%), rheumatological (13.8%), immunological (9.6%) and cardiac surgery (6.4%). A diagnosis of HLH was made by the treating clinical team in 30.9% and considered in the differential in a further 18.1%. Just 5 patients had complete data available to score against all 8 2004 HLH criteria whereas 49 patients had data to score against the modified criteria. Using all available data: 14/94 (14.9%) met ≥5/8 criteria and all these patients were diagnosed with HLH by the treating team. 33 (35.1%) met ≥4/5 criteria and 17 (51.5%) of these were diagnosed with HLH by clinicians. HLH was not documented as being considered in the differential in 11 (33.3%) Overall mortality was 33.0% (31/94) but was 17.2% (5/29) in those patients diagnosed with HLH during their admission. Conclusion: Although HEF is highly specific for HLH, the diagnosis was made or considered in just half of paediatric patients with this laboratory result. Increased awareness of this potentially-lethal condition is likely to lead to earlier treatment and reduced mortality. Acknowledgements: The following authors also contributed to this work – EL Long and F McErlane, Department of Paediatric Rheumatology, Great North Children's Hospital, Newcastle upon Tyne, UK, K McLellan, Department of Paediatric Rheumatology, Royal Hospital for Children, Glasgow, UK, K Gallagher and P Bale, Department of Paediatric Rheumatology, Addenbrooke's Hospital, Cambridge, UK, K Mahmood and C Pain, Department of Paediatric Rheumatology, Alder Hey Children's Hospital, Liverpool, UK